2009
DOI: 10.1167/iovs.08-2277
|View full text |Cite
|
Sign up to set email alerts
|

Optical Effects of Anti-TGFβ Treatment after Photorefractive Keratectomy in a Cat Model

Abstract: Purpose To assess the contribution of corneal myofibroblasts to optical changes induced by photorefractive keratectomy (PRK) in a cat model. Methods First, we tested the transforming growth factor β (TGFβ)-dependence of feline corneal keratocyte differentiation into α-smooth muscle actin (αSMA)-positive myofibroblasts in vitro. Twenty-nine eyes from 16 cats were then treated with −10D PRK in vivo and divided into two post-operative treatment groups: (1) eyes that received 100μg anti-TGFβ antibody for 7 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 40 publications
3
46
1
Order By: Relevance
“…Although multiple studies have demonstrated that scarring can be blunted by inhibiting the fibrosis pathway at the time of wounding (Blalock et al 2012; Buhren et al 2009; Huxlin et al 2013; Jester et al 1997; Sriram et al 2013; Talamo et al 1991), the current studies, to the best of our knowledge, are the first to demonstrate that an established model of human fibrosis can be reversed. Our previous studies on TGF-β3 (Karamichos et al 2011) have shown the prevention of scarring in vitro; however, in the present study, we attempted to reverse an established scar-like ECM.…”
Section: Discussionmentioning
confidence: 73%
“…Although multiple studies have demonstrated that scarring can be blunted by inhibiting the fibrosis pathway at the time of wounding (Blalock et al 2012; Buhren et al 2009; Huxlin et al 2013; Jester et al 1997; Sriram et al 2013; Talamo et al 1991), the current studies, to the best of our knowledge, are the first to demonstrate that an established model of human fibrosis can be reversed. Our previous studies on TGF-β3 (Karamichos et al 2011) have shown the prevention of scarring in vitro; however, in the present study, we attempted to reverse an established scar-like ECM.…”
Section: Discussionmentioning
confidence: 73%
“…According to the results, blocking TGF␤ signaling after PRK reduced corneal haze 51,52 and enhanced optical quality. 53 Although the efficacy of anti-TGF␤ therapy has been demonstrated in animals and related pharmaceutical approaches to the treatment of IPF are close to clinical trial, 54 an ideal antifibrotic therapeutic candidate has yet to be identified. In this study, ITE has proven to be a very effective inhibitor of TGF␤1 signaling in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research has focused on cat corneal endothelial cells (Huang et al, 1989; Petroll et al, 1999; Rotatori et al, 1994). Corneal scarring in response to corneal epithelial wound healing is also being studied in cats (Buhren et al, 2009; Huxlin et al, 2013). Cats, like rabbits, respond similarly to humans in terms of corneal scarring (Nagy et al, 2007).…”
Section: Ex Vivo Experimental Optionsmentioning
confidence: 99%